Mate choice for major histocompatibility complex (MHC) complementarity in the Yellow-rumped Flycatcher (Ficedula zanthopygia) - Mingju E; Xiaolei Song; Liufang Wang; Yimo Yang; Xianxiu Wei; Jiangping Yu; Ye Gong; Haitao Wang (Avian Research, 2021)
Abstract Background Genes of the major histocompatibility complex (MHC) are an important component of the vertebrate immune system and play a significant role in mate choice in animal populations. However, the MHC genetic targets of female mate choice have not been clearly identified, and whether female mate choice is based on neutral genetic characteristics remains an open question. Here, we focus on the effects of morphological traits and genetic similarity among individuals in MHC class IIB (MHC IIB) exon 2 on mating in a sexually dimorphic songbird that exhibits social monogamy with extra-pair paternity (EPP). Methods We sequenced 64 parent–offspring triads sampled over a 3-year period using two MHC class II loci to detect disassortative mating in the Yellow-rumped Flycatcher (Ficedula zanthopygia). Results We found that MHC similarity in social pairs was lower than that in random pairs. Extra-pair mate choice according to MHC IIB was observed, in which females’ extra-pair mates had fewer MHC alleles than their within-pair mates, but there was no significant band-sharing between extra-pair sires and potential extra-pair mates. However, the interaction between the MHC diversity of females and that of the social males affected the occurrence of EPP. Conclusions Our results support the “optimality hypothesis” of MHC-based social and extra-pair choice. Female choice probably maintains a certain level of MHC diversity in offspring in the Yellow-rumped Flycatcher.